Fabrication of Tannic Acid coated Polyglactin Surgical Suture to Prevent Bacterial Infection - Bakti Wahyu Saputra; Amelia Sendang Husin; Flavia Domitilla Erika Setyajati; Vincentia Krisnina Prasetyo; Skolastika Skolastika; Jeffry Julianus; Damiana Sapta Candrasari; Agustina Setiawati (Science Midwifery, 2022)
Polyglactin surgical (PLGA) suture is a b biodegradable raidedsuture frequently used in clinical surgery. Due to its braided structure, polyglactin suture is easier contaminated by bacterial during surgery process. Thus, this study was coated by tannic acid (TA) to prevent Staphylococcus aureus binding. Suture surface modification was carried out by immersing PLGA in tannic acid- ferri chloride (TA-Fe) solution pH 8. The fabrication process was confirmed by FTIR analysis, and the antibacterial preventing activity was determined by bioinformatics analysis. Thus, this engineered suture increased the wettability in DI water, serum, and saline solutions, which could be promising to increase the biocompatibility in wound healing process. To sum up, our method would be applied in surgical suture to prevent bacterial infection and potentially elevate the biocompatibility by increasing wettability in biological solutions.